Activeness of Visits to Integrated Healthcare Post and the Quality of Life among the Elderly in Peguyangan Kangin Village, North Denpasar, Bali - Ni Kadek Muliawati; Ni Luh Putu Dewi Puspawati (Poltekkes Kemenkes Palu, 2023)
The number of people aged over 60 years exceeds seven percent of the total world population which is currently in the era of aging population. Elderly Integrated Healthcare Post (Posyandu) provide social, religion, education, skills, sports, arts and culture services and other services with the aim of improving the quality of life of the elderly. This study aims to determine the relationship between activeness of visits to Posyandu and the quality of life among the elderly. This was a cross-sectional study conducted in Peguyangan Kangin Village, North Denpasar, Bali from April 2022-May 2022. The independent variable was the activeness of visits and the dependent variable was the quality of life of the elderly. The samples involved 158 respondents who were selected using a purposive sampling technique. Demographic data and questions related to quality of life were obtained by distributing questionnaires containing informed consent during the elderly Posyandu activities. Meanwhile, data on the activeness of the elderly for the last six months was taken from attendance data recorded by cadres in 10 banjars/hamlets. Bivariate analysis towards data with ordinal and nominal scales using the Spearman rho test obtained a p value of 0.873. Thus, statistically there was no relationship between the activeness of visits to Posyandu and the quality of life among the elderly in Peguyangan Timur Village, Denpasar. Healthcare workers and elderly Posyandu cadres are recommended to focus not only on the presence of the elderly at the Posyandu, but also try to implement the elderly Posyandu program properly.